Cytoprotective Effects of Natural Compounds against Oxidative Stress - Jay Mehta; Srujana Rayalam; Xinyu Wang (MDPI AG, 2018)
Oxidative stress, an imbalance between reactive oxygen species and antioxidants, has been witnessed in pathophysiological states of many disorders. Compounds identified from natural sources have long been recognized to ameliorate oxidative stress due to their inherent antioxidant activities. Here, we summarize the cytoprotective effects and mechanisms of natural or naturally derived synthetic compounds against oxidative stress. These compounds include: caffeic acid phenethyl ester (CAPE) found in honey bee propolis, curcumin from turmeric roots, resveratrol abundant in grape, and 1-[2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oyl] imidazole (CDDO-Im), a synthetic triterpenoid based on naturally occurring oleanolic acid. Cytoprotective effects of these compounds in diseases conditions like cardiovascular diseases and obesity to decrease oxidative stress are discussed.